Relationship and influences of behavioral and psychological factors on metabolic control of patients with type 2 diabetes mellitus - Stanojević, Vojislav; Jevtić, Marija; Mitrović, Milena; Panajotović, Marko; Aleksić, Aleksandar; Stanojević, Čedomirka (Vojnosanitetski pregled, 2023)
Background/Aim. Achieving good metabolic control, which plays a key role in reducing or preventing macrovascular and microvascular complications of diabetes mellitus (DM), requires continuous patient involvement in the self-management of DM. This continued engagement, which makes type 2 DM (T2DM) one of the most physically and emotionally demanding diseases, can become, at certain periods of life, extremely severe and lead to emotional distress (symptoms of depression and DM-related distress) and deterioration of metabolic control. The aim of this study was to examine the association and influence of behavioral and psychological factors on the metabolic control of patients with T2DM. Methods. The research was conducted as a descriptive-analytic cross-sectional study. The method of random sampling included 324 subjects with T2DM in the research. The values of biochemical parameters of metabolic control were measured by standard laboratory methods. Blood pressure was measured two times, and the arithmetic mean was calculated. Anthropometric measurement was performed, and body mass index (BMI) was calculated. Attitudes toward medication adherence, adherence to dietary recommendations, level of physical activity, presence of depressive symptoms, and level of DM-related distress were examined using standardized questionnaires. Results. The target values of metabolic control parameters were reached by 21.6% of respondents. Multivariate analysis as predictors of poor metabolic control identified obesity, non-adherence toward dietary recommendations, insulin therapy, low level of physical activity, and clinically significant DM-related distress. Conclusion. Routine application of the questionnaire used in this study in the initial stages or critical moments of the disease can assess patients’ attitudes and knowledge about behavioral determinants of DM self-management and timely detect psychological conditions that affect them. It would be realistic to expect that such a comprehensive holistic approach would contribute to a lower incidence of complications and better metabolic control of T2DM.